Cool cats and communities: Exploring the challenges and successes of community-based approaches to protecting felids from the illegal wildlife trade - Green, Aalayna R.; Anagnostou, Michelle; Harris, Nyeema C.; Allred, Shorna B. (Frontiers in Conservation Science, 2023)
Implementing community-based approaches to countering illegal wildlife trade is important to not only improve the effectiveness of strategies to protect wildlife, but also to promote equity and justice. We conducted an international exploratory review of interventions that aim to address the illegal trade in wildlife using a variety of community-based approaches. We focused our study on Felidae species in particular, as they factor centrally in the illegal wildlife trade, and have received significant conservation attention due to many being charismatic species. We searched for case studies that have been or are currently being implemented, and that were published between 2012-2022 in scholarly or grey literature databases. We extracted data on 40 case studies across 34 countries, including information on the approaches used, successes, challenges, and recommendations using a Theory of Change framework for community action on illegal wildlife trade. Initiatives to protect Felidae species from illegal trade could consider using multi-pronged approaches, consider historically underrepresented groups within communities - including women - in their design, and should evaluate the social and ecological outcomes to improve future efforts.